The enriched gut commensal Faeciroseburia intestinalis contributes to the anti-metabolic disorders effects of the Ganoderma meroterpene derivative - Shanshan Qiao; Kai Wang; Chang Liu; Nan Zhou; Li Bao; Jun Wang; Shuangjiang Liu; Hongwei Liu (Food Science and Human Wellness)
Previous study demonstrated that Ganoderma meroterpene derivative (GMD) increased the abundance of butyrate-producing bacteria in gut and subsequently delivered anti-metabolic disorder effect of host. To specify the key commensal bacteria associating with the beneficial effects, we tried to isolate and compare the microbiota from the cecal samples of GMD- and vehicle-treated ob/ob mice, and further identified butyrate-producing bacterial strains. It was found that Faeciroseburia intestinalis was enriched and 11 strains affiliated to F. intestinalis were cultivated from the gut of GMD-treated mice. In vitro assay attested butyrate production by representative strain of F. intestinalis. Oral administration with F. intestinalis further demonstrated its benefits on regulating hyperglycemia and hyperlipidemia, on decreasing plasma lipopolysaccharide (LPS) and inflammation, and on improving hepatic injuries. Treatment with F. intestinalis effectively enhanced the level of gut butyrate, which subsequently ameliorated the intestinal barrier function and activated epithelial PPAR-γ signaling pathway to regulate microbiome homeostasis in gut. Our study demonstrated that the causal relationship between the butyrate-producing bacteria and the GMD's therapeutic effects and confirmed the important function of the butyrate-producing F. intestinalis in maintaining host metabolism homeostasis.